2015
DOI: 10.3897/zookeys.540.9656
|View full text |Cite
|
Sign up to set email alerts
|

Resolving cryptic species complexes of major tephritid pests

Abstract: An (CRP)FAO/IAEA Co-ordinated Research Project on “Resolution of Cryptic Species Complexes of Tephritid Pests to Overcome Constraints to SIT Application and International Trade” was conducted from 2010 to 2015. As captured in the CRP title, the objective was to undertake targeted research into the systematics and diagnostics of taxonomically challenging fruit fly groups of economic importance. The scientific output was the accurate alignment of biological species with taxonomic names; which led to the applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 113 publications
2
70
0
4
Order By: Relevance
“…Moreover, the multidisciplinary approach used in integrative taxonomy revealed the presence of cryptic species (see De Meyer et al 2015a for a recent treatise of this in tephritid fruit flies). In groups of economic significance, such as Tephritidae, a proper identification is not only a prerequisite for any further research, be it fundamental or applied, but can also have serious political and economic consequences in aspects like control programs, quarantine regulations, and trade barriers (Hendrichs et al 2015). taxonomic recognition, preferably through different independent approaches, is a necessity and may facilitate accurate recognition of biological species (Clarke & Schutze 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the multidisciplinary approach used in integrative taxonomy revealed the presence of cryptic species (see De Meyer et al 2015a for a recent treatise of this in tephritid fruit flies). In groups of economic significance, such as Tephritidae, a proper identification is not only a prerequisite for any further research, be it fundamental or applied, but can also have serious political and economic consequences in aspects like control programs, quarantine regulations, and trade barriers (Hendrichs et al 2015). taxonomic recognition, preferably through different independent approaches, is a necessity and may facilitate accurate recognition of biological species (Clarke & Schutze 2014).…”
Section: Discussionmentioning
confidence: 99%
“…a case in particular is the description of C. quilicii sp. nov. this is the result of an integrative taxonomic study on a number of cryptic species complexes of economic significance (Hendrichs et al 2015), including the Ceratitis Far complex (Barr & wiegmann 2009;Virgilio et al 2008).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The source data is, for a large part, comprised of regional treatments (Drew 1989, Hancock and Drew 2006, White 2006, Drew and Romig 2013), with additions and revisions from more recent studies (Drew et al 2011, Yu et al 2012, Hancock 2015, Hancock and Drew 2015, Hendrichs et al 2015, Schutze et al 2015b, David et al 2016, 2017, Drew and Hancock 2016, Freidberg et al 2017, Han et al 2017). Species included in the list are ordered alphabetically by genus.…”
Section: Methodsmentioning
confidence: 99%
“…Another study which examined 193 tephritid species failed to discriminate six species in the B. dorsalis complex (B. dorsalis, B. occipitalis, B. carambolae, B. papaya, B. invadens, B. philippinensis) (Frey et al 2013;Jiang et al 2014). This discrepancy between taxonomic assignments and barcode results (Hendrichs et al 2015) provoked a reevaluation of their taxonomy, work which suggested that at least some of the taxa involved are conspecific (Khamis et al 2012;Schutze et al 2012). In fact, a subsequent taxonomic revision synonymized B. invadens and B. papaya with B. dorsalis (Schutze et al 2015).…”
Section: Incomplete Resolution or Flawed Taxonomy?mentioning
confidence: 97%